Parkinson’s Disease and Food Expenditure in Italy: Stochastic and Non-Stochastic Analyses - Cornelli, Umberto; Iftime, Maria Daniela; Malnati, Sofia; Mandelli, Kevin; Masini, Chiara; Messina, Beatrice; Nebbia, Stefano; Piarulli, Gabriele; Piccinini, Daniele; Pulecchi, Francesca; et al. (British Journal of Healthcare and Medical Research, 2024)
Background: The correlation between food and Parkinson’s disease (PD) suggests the Mediterranean diet (MeD) could provide beneficial effects. Objective: Examine the association between PD and food expenditure/consumption in various regions of Italy in 2016. Methods: The food consumption of 19,500 families in 540 Italian municipalities, recorded both in terms of expenditure and weight (kilograms) across 56 distinct food categories, was calculated for the year 2016, along with the Parkinson’s Disease prevalence expressed in terms of standardized mortality ratio (SMR). The correlations to Parkinson’s disease were determined using stochastic analysis based on partial least squares regression (PLSR) and non-stochastic analysis (neural network mapping). Results: The following results were obtained by focusing on food categories deemed significant in both stochastic and non-stochastic Analyses: Yogurt, fresh vegetables, wine, processed meat, citrus fruit, and butter were identified as causative factors, while cheese, ice cream, beef, grapes and strawberries, bananas, canned fruit, and fruit juice were deemed partially causative. Added sugar, flour, lamb, and dried legumes emerged as having protective properties, while seed oil, pork, fish, canned fish, and canned tomatoes exhibited only partially protective effects. Southern Italy has a significantly lower SMR for PD compared to the North due to lower consumption of foods found to be causative for PD and higher consumption of protective foods. Conclusions: In 2016, the PD death rate was significantly lower in Southern Italy than in the North. The dietary habits in the Southern regions were also significantly different: a lower consumption of causative foods and higher consumption of protective ones. The data on food expenditure and quantities allow us to monitor the correlation with PD SMR on an annual basis.